The Effect of Civics Learning on Self-Control for Fifth Grade Students at SDN 118 Matajang, Camba District, Maros Regency - Andi Sugiati; Musdalifah Syahrir (Universitas of Muhammadiyah Makassar, 2022)
The main problem in this study is whether Civics learning influences the Self Control of fifth-grade students at SDN 118 Matajang, Camba District, Maros Regency. This type of research is ex post facto research with quantitative methods. This study aims to determine the effect of Civics learning on the Self Control of the fifth-grade students of SDN 118 Matajang, Camba District, Maros Regency, amounting to 38 people. The research instruments used to collect data were Observation, Documentation, Questionnaire, and Test. The results showed that the data were analyzed using descriptive, correlation, and the Coefficient of Determination Test. Data were analyzed using the technique. Descriptive statistical analysis found that the pretest's average value (mean) was 66.18 and was in a low category, namely 53. While the average (mean) of the post-test was 90.11 and was in the high category, namely 95. In correlation analysis using Correlation Coefficient Interpretation, it can be seen that the correlation of the two variables is in a Strong category because the value of T Count 0.616 is greater than the r-table 0.329 at a significant level of 5%. For the Coefficient of Determination test, the coefficient of determination is 0.379, which means Civics Learning affects Self-Control, which is 37.9%. Then obtained Tcount Table or 0.616 0.329 so it can be concluded that the proposed hypothesis is accepted (Ha). This means that Civics learning affects the Self Control of students at SDN 118 Matajang, Camba District, Maros Regency.